Intravesical vancomycin for the treatment of Corynebacterium cystitis and struvite bladder stones: A case report - Jason E. Michaud; Christian C. Morrill; Ahmad Haffar; Heather N. Di Carlo; John P. Gearhart (Urology Case Reports)
Urologic patients with anatomic abnormalities can be particularly susceptible to urinary tract infections (UTI). UTI with urease-producing bacteria can promote struvite urinary calculi and pose unique treatment problems. There is potential for rapid stone growth and bacterial eradication can be difficult secondary to urothelial or stone colonization. Antibiotic resistance among urease-producing organisms further complicates treatment. In this report, we describe the use of intravesical vancomycin in the treatment of a patient with struvite bladder calculi secondary to urease-producing Corynebacterium urealyticum cystitis, resistant to enteral antibiotics. This highlights the potential of intravesical antibiotics for the treatment of UTI.